2023
DOI: 10.1177/08862605221145954
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Severity of Sexual Harassment, and its Impact on Mental Health in a Cohort of International Humanitarian Field-Workers

Abstract: To date, there have been no cohort studies of sexual harassment incidence and its relation to mental health within humanitarian field-workers. Research among numerous occupations suggests an association between workplace sexual harassment and several health complaints. This study examined the incidence and severity of sexual harassment and its association with changes in mental health in a cohort of international humanitarian aid field-workers (iHAWs). Four hundred and seventy-eight iHAWs filled in questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Zhu et al (2019), however, have stressed that sexual harassment is an unwanted sexual action directed against another person, and hence it may occur in both men and women. According to Cho (2002) and Martinmaki et al (2023), sexual harassment is any unwelcome sexual activity, whether physical, verbal, or with particular signals, that has a detrimental influence on workers' performance at work. Welsh (1999), he indicated that sexual harassment falls into two categories: hostile environment harassment and quid pro quo.…”
Section: Literature Review Workplace Sexual Harassmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al (2019), however, have stressed that sexual harassment is an unwanted sexual action directed against another person, and hence it may occur in both men and women. According to Cho (2002) and Martinmaki et al (2023), sexual harassment is any unwelcome sexual activity, whether physical, verbal, or with particular signals, that has a detrimental influence on workers' performance at work. Welsh (1999), he indicated that sexual harassment falls into two categories: hostile environment harassment and quid pro quo.…”
Section: Literature Review Workplace Sexual Harassmentmentioning
confidence: 99%
“…Sexual harassment is a pervasive issue that affects workplaces worldwide (Cho, 2002). Following the #MeToo movement, the issue of sexual harassment in the workplace has received increased attention (Martinmaki et al, 2023), and the International Labor Organization has recognized it as a global phenomenon (Beghini, 2021). Notably, the Middle East and North Africa region has been identified as the least advanced in terms of legislation addressing sexual harassment in the workplace (Alquisi and Sryreh, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This substantial body of research shows that both SH and GH are associated with decrements to mental health including increased depression, anxiety, and suicidal ideation [ 8 , 13 , 14 ]. Recent cross-sectional research continues to show associations between SH and greater symptoms of depression, anxiety, suicidality, or poor mental well-being in samples as varied as women soldiers in Belgium [ 15 ], men and women medical school faculty in the Midwestern US [ 16 ], men and women medical students in France [ 17 ] and Switzerland [ 18 ], and international humanitarian field workers [ 19 ]. Research on GH, or closely related constructs such as workplace bullying, is not as common as SH research.…”
Section: Introductionmentioning
confidence: 99%